A report on the practice-in-industry training in the fish culture - Avelino, Marcial Manzanero (College of Fisheries, University of the Philippines, 1958)
The practice in industry is a prerequisite after a student has finished his two years fishery course. This will help them to reform the student their shortcoming while in school and this will train them to apply their theoretical knowledge to practical or actual field. The practice in industry was undergone in Ragay, Camarines Sur inclusive from the months of June to September. The first month of training was made in the fishpond of Mr. Genaro Cuala which was under development. The second and the third months of practice (July to August of year 1958) was conducted in the fishpond of Mr. Abraham Ronquillo. The fourth or last month of training was done in the fishpond of Mr. Germogenes Pormento. The problem on the eradication of monovalve (Telescopium sp.) in this fishpond was unfinished, however, solutions to solve this problem were left to the owner.